Relationship between coping mechanisms to psychosocial stress with blood pressure in young adults: a pilot study - Aung, Sithu; Musa, Ramli; Ab Rahman, Jamalludin; Mohd Shah, Azarisman Shah; Abdullah, Aszrin (Ibn Sina Trust, 2018)
Background: Hypertension is a major risk factor for cardiovascular diseases, one of the leading causes of death worldwide. Prehypertension is a precursor of hypertension, with high prevalence in young adults. Psychosocial stress can be one of the modifiable risk factors for hypertension. The objective of the study is to assess the relationship between coping mechanism to psychosocial stress and the blood pressure of young adults.